Exercise Therapy is Efficacious in Reducing Pain of Musculoskeletal Disorders in Cleaning Workers: A Systematic Review - Fikri, Fikri; Rekawati, Etty; Permatasari, Henny (GLOBAL HEALTH SCIENCE GROUP, 2024)
Musculoskeletal disorders (MSDs) are conditions that lower productivity, cause discomfort in the form of decreased range of motion or chronic pain and impair function. These can be made worse by the workplace and its surroundings, and they impact the muscles, bones, nerves, tendons, ligaments, joints, cartilage, and intervertebral discs. Exercise therapy is one non-pharmacological intervention that might be helpful in reducing pain complaints related to MSDs. This study aimed to review the literature regarding the efficacy of exercise therapy in mitigating pain associated with musculoskeletal disorders (MSDs) in cleaning workers. A systematic review was the methodology employed. Searches for articles published between 2013 and 2023 were conducted using Google Scholar, PubMed, ProQuest, and Science Direct. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach, the search strategy was conducted. Five of the articles were eligible for inclusion. Four studies employed a quasi-experimental design, and one study used an RCT design. Exercise therapy, which includes aerobic, motor control, functional, ergonomic, and foam roller exercises, was found to be beneficial in lowering musculoskeletal pain in cleaning workers across all studies. This evidence suggests that exercise therapy can be used as a nursing intervention to reduce musculoskeletal pain in cleaning workers.